Haemostasis in Haemophilia in Relation to the Haemostatic Balance in the Normal Organism and the Effect of Pea Nuts - Astrup, Tage; Brakman, Pieter; Ollendorff, Preben; Rasmussen, jørgen (Thrombosis and Haemostasis, 1961)
The problems of haemostasis in haemophiloid patients are considered on the basis of a dynamic equilibrium between fibrin formation and fibrin resolution. It is suggested that the observation by Boudreaux and Frampton of an orally acting haemostatic factor in pea nuts is a result of a delayed fibrin resolution, caused by an antifibrinolytic compound, and not of a restoration of the plasma thromboplastin system (the antihaemophilic factor). This assumption is supported by the results of some preliminary experiments. The haemophiloid disorders represent a deviation in the normal haemostatic balance. For this reason they acquire a broader significance in the study of the physiology and pathology of tissue repair processes than represented by the number of patients carrying these diseases. Some implications concerning the pathogenesis of arteriosclerotic lesions are suggested.